E-102 Policy, practice and science in Nigeria: Implementing evidence based research for HIV programming in Nigeria. (April 2018) - Adewole, Isaac F.
Abstract : Nigeria with a population of over 180 million currently has a national estimate of 3% prevalence of HIV infection. Briefly, 3 million people are living with HIV; 160, 000 pregnant women living with HIV and pediatric HIV infection account for about 30% of global burden. Following the assumption of office by President Muhammadu Buhari in 2015, the country initiated plan and began an aggressive drive in revitalizing the healthcare system towards attainment of Universal Health Coverage in the country. This presentation will chronicle policies, practices and evidences generated in-country on biology of HIV infection, transmission and management as well other non-orthodox claims of cure. The socio-cultural interpretations, perceptions and behaviours as it affects HIV infection within Nigerian space will be highlighted. The concluding section of the presentation will focus on key priority areas of HIV programming and research that requires international collaborations.